An Evaluation of Thyroid Function in Preeclampsia (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Pregnancy is associated with reversible physiological changes in thyroid function which is well documented. These changes in thyroid function have been considered as one of the pathophysiological causes of preeclampsia. Pre-eclampsia is an elusive condition to diagnose and a complex disease to manage. The aim of the study is to determine the association of reduced thyroid function with preeclampsia.Materials and methods: This cross sectional study was carried out in the Department of Obstetrics & Gynecology. Bangabandhu Sheikh Mujib Medical University, Dhaka between October 2015 and August 2016. A total of 70 pregnant women between 18 and 35 years of age attending outdoor antenatal clinic were enrolled in this study. Among them 35 pregnant women with clinical diagnosis of preeclampsia were considered as case and group I, and rest 35 apparently healthy normotensive pregnant women were considered as control and group II. Blood samples were collected and estimated for TSH and FT4. Statistical analysis of the results was obtained by using Windows based computer software devised with Statistical Packages for Social Sciences (SPSS-22).Results: The mean TSH levels were significantly higher (p3.5 μIU/ml in preeclamptic women was 3.8 (95% CI 1.2 to 11.6%). Significant positive correlations were found between TSH levels with systolic blood pressure, diastolic blood pressure and proteinuria in preeclampsia group (r=0.550, p=0.001, r=0.644, (p=0.001) and r=0.618, p= 0.001 respectively).Conclusion: Abnormal TSH titer is associated with the risk of occurrence of preeclampsia and its severity.JCMCTA 2022 ; 33 (2) : 113-119